2005
DOI: 10.1002/jbm.b.30204
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the dog as a model for human total hip replacement: Analysis of 38 postmortem‐retrieved canine cemented acetabular components

Abstract: Thirty-eight cemented acetabular components that had been clinically implanted in client-owned dogs were retrieved postmortem and analyzed for mechanical stability, volumetric wear, and articular surface damage. Comparison of the results from this study with similar studies on autopsy-retrieved human components will provide insight into the adequacy of the dog as a model for human total hip replacement (THR). The canine average volumetric wear rate (6.7 +/- 4.2 mm(3) per year) was an order of magnitude lower t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
79
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(83 citation statements)
references
References 32 publications
2
79
0
2
Order By: Relevance
“…In vivo paracrine and autocrine signalling cascades leading to bone formation are complex and rely on strict spatiotemporal interplay between select growth factors. Teasing apart the individual roles that each growth factor plays within bone development and healing systems is of the highest (Aerssens et al, 1998;Kimmel and Jee, 1982;Neyt et al, 1998;Pearce et al, 2007;Skurla and James, 2005) (Aerssens et al, 1998;Mosekilde et al, 1993;Pearce et al, 2007;Thorwarth et al, 2005) Primates (Aerssens et al, 1998;Newman et al, 1995;Pearce et al, 2007;Ravaglioli et al, 1996) (Castaneda et al, 2006;Liebschner, 2004;Pearce et al, 2007) (Aerssens et al, 1998;Gomes and Fernandes, 2010;Liebschner, 2004;O'Loughlin et al, 2008) Table 4. Organic, inorganic and synthetic materials for orthopaedic applications in vivo.…”
Section: Individual Growth Factorsmentioning
confidence: 99%
“…In vivo paracrine and autocrine signalling cascades leading to bone formation are complex and rely on strict spatiotemporal interplay between select growth factors. Teasing apart the individual roles that each growth factor plays within bone development and healing systems is of the highest (Aerssens et al, 1998;Kimmel and Jee, 1982;Neyt et al, 1998;Pearce et al, 2007;Skurla and James, 2005) (Aerssens et al, 1998;Mosekilde et al, 1993;Pearce et al, 2007;Thorwarth et al, 2005) Primates (Aerssens et al, 1998;Newman et al, 1995;Pearce et al, 2007;Ravaglioli et al, 1996) (Castaneda et al, 2006;Liebschner, 2004;Pearce et al, 2007) (Aerssens et al, 1998;Gomes and Fernandes, 2010;Liebschner, 2004;O'Loughlin et al, 2008) Table 4. Organic, inorganic and synthetic materials for orthopaedic applications in vivo.…”
Section: Individual Growth Factorsmentioning
confidence: 99%
“…Figure 12 reveals a missing section of the surface near 12 o'clock for each canine liner. Canine components are manufactured with a dorsal cutout in this location that complicates volumetric analysis 44. As in previous studies,23 the initial radii to which the worn liners were compared were assessed from the unworn regions.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Skurla and James of 38 retrieved canine UHMWPE liners44 found significant positive correlation between total volumetric wear, and both articulating surface damage score and implant duration. They measured volumetric wear by the oil drop method, arguably the best technique for retrieval studies with no initial state control.…”
Section: Discussionmentioning
confidence: 99%
“…The domestic dog is one such long-lived mammal that is used as a model in orthopedic and dental studies (16). Changes in the skeletal system of canines occur both in young and old dogs, and osteoporotic changes or osteoarthritis are similar in nature to those observed in elderly humans (17). Mn and Fe belong to the group of essential elements.…”
Section: Introductionmentioning
confidence: 99%